Changes in the Blood in Liver Diseases and Modern Clinical Diagnostic Methods (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Many liver biochemical tests can assess liver function by measuring the amount of enzymes released into the bloodstream (e.g., aminotransferase from damaged liver cells, alkaline phosphatase in cholestasis) or hepatobiliary excretion (e.g., bilirubin). Other tests are used to assess the synthetic function of the liver (e.g., prothrombin time [PT], usually international normalized ratio [INR]; albumin).The most useful tests for screening for various liver diseases are serum aminotransferase levels (the most commonly measured liver function tests), bilirubin, and alkaline phosphatase. Certain biochemical abnormalities can help distinguish hepatocellular pathology from biliary tract disorders (cholestasis - see table of most common laboratory abnormalities). Tests for the diagnosis of viral hepatitis, liver inflammation, or immune disorders include serological tests for markers of hepatitis viruses and measurements of immunoglobulins, antibodies, and autoantibodies.